Towards linguistics competence for agricultural technician students controlled to free writing techniques - Picardal, Teresita F. (Tomas) 1936- (1974)
This is a proposal on the use of controlled to free writing techniques as tools towards linguistic competence. Along with this, materials in writing which use graded controlled to free writing techniques geared to the needs of students enrolled in the Revised Two-year Agricultural Technician Curriculum was presented. The materials are designed to supplement the oral and written exercises found in textbooks for teaching writing in College Freshman English.
Thesis (M.A.T.English as a second language)--University of the Philippines.
Keywords: English language -- Rhetoric; English language -- Study nd teaching -- Filipino students